A VARIANT OF RSA CRYPTOSYSTEM ON THE ENDOMORPHISM RING End(Z_n×Z_(n^k )) - Long, Tran Dinh; Nga, Le Thi Kim (Hue University Journal of Science: Natural Science, 2018)
Based on the arithmetic of the endomorphisms ring End(Zp X Zpk), the paper constructs an exponent type encryption and decryption cryptosystem. Althought involving more operations in encryption and decryption phases than that of original RSA one, the cryptosystem has some advantages in avoiding lattice and chosen plaintext attacks compared to original RSA cryptosystem.